Anti-fatigue aluminum alloy bar and preparation method thereof
By combining the porous composite ceramic skeleton with the metamorphic aluminum alloy, a fatigue-resistant aluminum alloy rod was prepared, which solved the problem of the existing aluminum alloy materials being prone to fatigue under harsh conditions, achieved higher mechanical properties and fatigue resistance, and was suitable for more rigorous application environments.
Patent Information
- Application Number
- CN202411948276.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
Existing aluminum alloy materials are prone to fatigue cracks under harsh service conditions, resulting in component failure, and their mechanical properties and fatigue resistance are not sufficient to meet more stringent application needs.
The porous composite ceramic skeleton is combined with the deformed aluminum alloy to prepare fatigue-resistant aluminum alloy rods by hot extrusion. The material consists of 90-95% by weight of the metamorphic aluminum alloy and 5-10% by weight of the porous composite ceramic frame. The high strength and hardness of the ceramic frame are used to combine the high plasticity and high toughness of the metamorphic aluminum alloy to achieve complementary performance.
While maintaining the low density of the material, the comprehensive mechanical properties and fatigue resistance of aluminum alloys are significantly improved, and its service life and reliability under harsh conditions are enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloys, and in particular to a fatigue-resistant aluminum alloy bar. Background Art
[0002] Aluminum alloys have the characteristics of low density, good electrical and thermal conductivity, and high specific strength. They meet the current needs of energy conservation, emission reduction, and green environmental protection in industrial development, and have good applications in aerospace, automobile manufacturing, weapons, and other fields. At the same time, aluminum is abundant in the earth's crust and has good processing performance. Therefore, aluminum alloys have low costs and broad application prospects, and have received widespread attention. In order to meet more stringent service conditions, broaden the application scope of aluminum alloys, and extend the service life of aluminum alloys, it is necessary to further improve the mechanical properties and fatigue resistance of aluminum alloys and prepare aluminum alloys with better comprehensive performance. The mechanical properties and fatigue resistance of aluminum alloys depend on comprehensive factors such as composition, organization, and stress. Adding modifiers to purify the alloy melt can improve the alloy's organizational morphology and eliminate defects in the material. In addition, compounding different forms of reinforcements in the alloy, such as nanoparticles and continuous fibers, can improve the alloy's microstructure and prevent the migration and expansion of defects within the alloy. These methods can effectively improve the comprehensive performance of aluminum alloys and further expand the scope of application of aluminum alloys. Summary of the invention
[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a fatigue-resistant aluminum alloy bar.
[0004] Technical solution: A fatigue-resistant aluminum alloy rod, which is composed of a porous composite ceramic skeleton and a modified aluminum alloy, including 90-95wt% of the modified aluminum alloy and 5-10wt% of the porous composite ceramic skeleton. Preferably, the modified aluminum alloy has the following composition: Si: 16.0~18.0wt%; Cu: 4.0~5.0wt%; Mg: 0.4~0.6wt%; Fe: ≤0.5wt%; Zn: ≤0.2wt%; Mn: ≤0.1wt%; Modifier: 0.4~0.5wt%; the balance is Al. Preferably, the aluminum alloy modifier is composed of the following parts by weight: P: 10-20 parts; La: 40-45 parts; Gd: 40-45 parts. Preferably, the porous composite ceramic skeleton consists of cubic boron nitride and aluminum nitride. Preferably, the preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Adding gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grinding with a grinder for 1 to 2 hours at a speed of 100 to 120 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry is loaded into a centrifugal device and centrifuged at a temperature of -30 to -20°C for 40 to 60 minutes at a speed of 800 to 1200 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, and the vacuum is reduced to 5 to 10 Pa. The surface temperature of the sample is maintained at -30 to -20 ° C for 45 to 50 hours. After the surface of the sample is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: first heat the green body to 600-620°C at a heating rate of 4-8°C / min, keep it warm for 80-100 minutes, remove the binder and dispersant, then heat it to 1400-1500°C at a heating rate of 6-10°C / min, keep it warm for 100-120 minutes, and finally cool it to room temperature to obtain a porous composite ceramic skeleton. Preferably, the ceramic slurry comprises the following components: 20-30wt% cubic boron nitride particles, 10-20wt% alumina particles, 0.6-1wt% polyacrylic acid as a dispersant, 0.5-1wt% gelatin as a binder, and the remainder being water. Preferably, the aluminum alloy bar is prepared by hot extrusion, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 500-600 MPa for 10-20 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body is placed in a plasma discharge sintering furnace, evacuated to 5-10 Pa, an axial pressure of 30-40 MPa is applied, and the green body is heated to 500-600 ° C at a heating rate of 40-60 ° C / min, kept at this temperature for 10-15 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet is kept at 480-520°C for 20-30 min, put into an extruder for extrusion at a speed of 2-5 mm / s, and cooled to room temperature to obtain an aluminum alloy rod. Preferably, the porous composite ceramic skeleton has a porosity of 65-75% and a pore size range of 200-300 μm. Preferably, the aluminum alloy particles have a particle size of 20 to 40 μm. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The aluminum alloy rod described in the present invention is composed of a porous composite ceramic skeleton and a modified aluminum alloy. It can combine the high plasticity and toughness of the aluminum alloy with the high strength, high hardness and high wear resistance of the ceramic material. On the premise of maintaining the low density of the material, it achieves the complementarity of the alloy and ceramic properties and improves the comprehensive mechanical properties of the aluminum alloy. Silicon has high hardness and low density. It can be used as a hard point in the aluminum alloy matrix to improve the strength and wear resistance of the alloy, while improving the airtightness and fluidity of the alloy melt and optimizing the casting processability. However, without special treatment, the primary silicon and eutectic silicon in the alloy matrix are mostly in the form of laths and irregular blocks, and are unevenly distributed. Under harsh service conditions, the tip of the eutectic silicon is prone to fatigue cracks in the matrix, resulting in failure of the alloy component. Therefore, adding a modifier to the alloy improves the morphology of primary silicon and eutectic silicon, making them small and round, and evenly distributed, which can reduce their weakening effect on the organization and improve the mechanical properties and fatigue resistance of the alloy. Commonly used modifiers in aluminum silicon alloys include P, Sr, rare earth, etc. Each modifier has a different mechanism of action and has its own advantages and limitations. P element modification mainly forms AlP particles in the alloy, providing heterogeneous nucleation sites for primary silicon, which plays a role in refining size and uniform distribution. Rare earths improve the size and morphology of eutectic silicon by being adsorbed on the sharp corners of the silicon phase, thus playing a role in modification. In addition, rare earths are also oxygen-affinity, which can play a role in refining, removing hydrogen, and purifying the melt. Mixed rare earths can also produce new phases at the grain boundaries, playing a role in dispersion strengthening. Therefore, the use of P+light rare earth+heavy rare earth composite modifiers can simultaneously improve the morphology of primary silicon and eutectic silicon, refine the size of the silicon phase, purify the alloy melt, and improve the mechanical properties and fatigue resistance of the aluminum alloy. Ceramics have high strength, high hardness and high thermal stability. As a reinforcement for metal materials, they can make the comprehensive performance of the materials better and have a wider range of applications. The hardness of cubic boron nitride is second only to diamond, and its thermal stability is higher than that of diamond. When added to aluminum alloys, it can improve the strength and hardness of the alloys, but the sintering performance of cubic boron nitride is poor. Adding aluminum nitride as a binder can make it better bonded to the matrix and ensure the performance and stability of the composite material. Ceramic reinforcements are usually divided into the form of particles, whiskers and fibers, most of which are one-dimensional or two-dimensional structures with various anisotropies, which are not conducive to improving the overall performance of the alloy. Porous ceramics have a three-dimensional network structure with various isotropies, and the porous structure has a large specific surface area and high surface energy. It can fully contact and bond with the metal matrix, which can effectively improve the comprehensive performance of the alloy. Compared with the prior art, the present invention has the following advantages and positive effects: The present invention adds a P+light rare earth+heavy rare earth composite modifier to the hypereutectic aluminum silicon alloy, which can effectively improve the size, morphology and distribution of primary silicon and eutectic silicon, and improve the mechanical properties and fatigue resistance of the alloy. The present invention uses porous composite ceramics to strengthen the aluminum alloy matrix. The composite ceramics can improve the sintering strength, and the porous structure has isotropic properties, which can effectively enhance the comprehensive mechanical properties of the aluminum alloy. The present invention uses sintering and hot extrusion methods to prepare composite aluminum alloy rods, the preparation method is simple, the processing efficiency is high, the rod size is controllable, and the formability is good. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A fatigue-resistant aluminum alloy rod, the aluminum alloy rod is composed of a porous composite ceramic skeleton and a modified aluminum alloy, including 90wt% of the modified aluminum alloy and 10wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 16.0wt%; Cu: 5.0wt%; Mg: 0.4wt%; Fe: 0.5wt%; modifier: 0.5wt%; the balance is Al; the aluminum alloy modifier is composed of the following parts by weight: P: 10 parts; La: 45 parts; Gd: 45 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 2 hours at a speed of 100 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -30°C for 60 min at a speed of 800 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 5 Pa, and the sample surface temperature is maintained at -30 ° C for 50 h. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 600°C at a heating rate of 4°C / min, keep the temperature for 80min, remove the binder and dispersant, then heat to 1400°C at a heating rate of 6°C / min, keep the temperature for 100min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 30wt% cubic boron nitride particles, 10wt% alumina particles, 1wt% polyacrylic acid as a dispersant, 1wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 600 MPa for 10 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body is placed in a plasma discharge sintering furnace, evacuated to 5 Pa, an axial pressure of 40 MPa is applied, and the green body is heated to 500 ° C at a heating rate of 40 ° C / min, kept at this temperature for 10 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 480°C for 30 min, placed in an extruder for extrusion at a speed of 2 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 65% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Embodiment 2: A fatigue-resistant aluminum alloy rod, the aluminum alloy rod is composited by a porous composite ceramic skeleton and a modified aluminum alloy, including 95wt% of the modified aluminum alloy and 5wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 18.0wt%; Cu: 4.0wt%; Mg: 0.6wt%; Zn: 0.2wt%; Mn: 0.1wt%; Modifier: 0.4wt%; Balance is Al; The aluminum alloy modifier is composed of the following parts by weight: P: 20 parts; La: 40 parts; Gd: 40 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1 h at a speed of 120 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -20°C for 40 min at a speed of 1200 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 10 Pa, and the sample surface temperature is maintained at -20 ° C for 45 h. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 620°C at a heating rate of 8°C / min, keep the temperature for 100min, remove the binder and dispersant, then heat to 1500°C at a heating rate of 10°C / min, keep the temperature for 120min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 20wt% cubic boron nitride particles, 20wt% alumina particles, 0.6wt% polyacrylic acid as a dispersant, 0.5wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 500 MPa for 20 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 10 Pa, an axial pressure of 30 MPa was applied, and the green body was heated to 600 ° C at a heating rate of 60 ° C / min, kept at this temperature for 15 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 520°C for 20 min, placed in an extruder for extrusion at a speed of 5 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 75% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Embodiment 3: A fatigue-resistant aluminum alloy rod, the aluminum alloy rod is composited by a porous composite ceramic skeleton and a modified aluminum alloy, including 92wt% of the modified aluminum alloy and 8wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 17.2wt%; Cu: 4.1wt%; Mg: 0.45wt%; Fe: 0.27wt%; Zn: 0.13wt%; Mn: 0.07wt%; Modifier: 0.45wt%; Balance is Al; The aluminum alloy modifier is composed of the following parts by weight: P: 12 parts; La: 43 parts; Gd: 45 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1.5 hours at a speed of 115 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -23°C for 50 min at a speed of 900 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, and the vacuum is reduced to 8 Pa. The surface temperature of the sample is maintained at -23 ° C for 46 hours. After the surface of the sample is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 605°C at a heating rate of 6°C / min, keep the temperature for 90min, remove the binder and dispersant, then heat to 1420°C at a heating rate of 7°C / min, keep the temperature for 110min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 27wt% cubic boron nitride particles, 13wt% alumina particles, 0.8wt% polyacrylic acid as a dispersant, 0.8wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 540 MPa for 15 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 8 Pa, an axial pressure of 36 MPa was applied, and the temperature was heated to 530 ° C at a heating rate of 45 ° C / min, kept at this temperature for 13 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 500°C for 25 min, placed in an extruder for extrusion at a speed of 4 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 70% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Embodiment 4: A fatigue-resistant aluminum alloy rod, the aluminum alloy rod is composited by a porous composite ceramic skeleton and a modified aluminum alloy, including 94wt% of the modified aluminum alloy and 6wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 16.4wt%; Cu: 4.8wt%; Mg: 0.51wt%; Fe: 0.15wt%; Zn: 0.07wt%; Mn: 0.02wt%; Modifier: 0.43wt%; Balance is Al; The aluminum alloy modifier is composed of the following parts by weight: P: 17 parts; La: 42 parts; Gd: 41 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1.2 h at a speed of 110 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -25°C for 55 min at a speed of 1000 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 6 Pa, and the sample surface temperature is maintained at -25 ° C for 48 hours. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 615°C at a heating rate of 7°C / min, keep the temperature for 95min, remove the binder and dispersant, then heat to 1480°C at a heating rate of 9°C / min, keep the temperature for 115min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 22wt% cubic boron nitride particles, 18wt% alumina particles, 0.7wt% polyacrylic acid as a dispersant, 0.5wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 580 MPa for 12 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 6 Pa, an axial pressure of 33 MPa was applied, and the temperature was heated to 570 ° C at a heating rate of 55 ° C / min, kept at this temperature for 15 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 490°C for 28 min, placed in an extruder for extrusion at a speed of 3 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 68% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Embodiment 5: A fatigue-resistant aluminum alloy rod, the aluminum alloy rod is composited by a porous composite ceramic skeleton and a modified aluminum alloy, including 93wt% of the modified aluminum alloy and 7wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 17.6wt%; Cu: 4.5wt%; Mg: 0.58wt%; Fe: 0.39wt%; Zn: 0.19wt%; Mn: 0.05wt%; Modifier: 0.48wt%; The balance is Al; The aluminum alloy modifier is composed of the following parts by weight: P: 15 parts; La: 42 parts; Gd: 43 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1.8 hours at a speed of 105 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -27°C for 45 min at a speed of 1100 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 9 Pa, and the sample surface temperature is maintained at -27 ° C for 47 hours. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 610°C at a heating rate of 5°C / min, keep the temperature for 85min, remove the binder and dispersant, then heat to 1460°C at a heating rate of 8°C / min, keep the temperature for 105min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The ceramic slurry has a composition ratio of: 25 wt % cubic boron nitride particles, 15 wt % alumina particles, 0.8 wt % polyacrylic acid as a dispersant, 0.7 wt % gelatin as a binder, and the balance being water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 520 MPa for 18 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 7 Pa, an axial pressure of 38 MPa was applied, and the temperature was heated to 550 ° C at a heating rate of 50 ° C / min, kept at this temperature for 12 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 510°C for 23 min, placed in an extruder for extrusion at a speed of 4 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 72% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Comparative Example 1: An aluminum alloy rod, the aluminum alloy rod is composited by a porous composite ceramic skeleton and an aluminum alloy, including 90wt% of the aluminum alloy and 10wt% of the porous composite ceramic skeleton; The aluminum alloy composition is as follows: Si: 16.8wt%; Cu: 4.6wt%; Mg: 0.44wt%; Fe: 0.17wt%; Zn: 0.10wt%; Mn: 0.08wt%; the balance is Al; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1.7 hours at a speed of 105 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -28°C for 50 min at a speed of 1000 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 7Pa, and the sample surface temperature is maintained at -28°C for 49h. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 610°C at a heating rate of 6°C / min, keep the temperature for 85min, remove the binder and dispersant, then heat to 1450°C at a heating rate of 8°C / min, keep the temperature for 100min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 24wt% cubic boron nitride particles, 16wt% alumina particles, 0.6wt% polyacrylic acid as a dispersant, 0.6wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 550 MPa for 14 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 8 Pa, an axial pressure of 35 MPa was applied, and the temperature was heated to 590 ° C at a heating rate of 50 ° C / min, kept at this temperature for 11 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 500°C for 26 min, placed in an extruder for extrusion at a speed of 3 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 67% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Comparative Example 2: An aluminum alloy rod, the aluminum alloy rod is composited by a porous composite ceramic skeleton and a modified aluminum alloy, comprising 92wt% of the modified aluminum alloy and 8wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 17.5wt%; Cu: 4.1wt%; Mg: 0.52wt%; Fe: 0.19wt%; Zn: 0.10wt%; Mn: 0.08wt%; Modifier: 0.41wt%; The balance is Al; The aluminum alloy modifier is P; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1.4 h at a speed of 110 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -22°C for 60 min at a speed of 900 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 10 Pa, and the sample surface temperature is maintained at -22 ° C for 48 h. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 605°C at a heating rate of 4°C / min, keep the temperature for 80min, remove the binder and dispersant, then heat to 1430°C at a heating rate of 9°C / min, keep the temperature for 110min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 28wt% cubic boron nitride particles, 12wt% alumina particles, 0.7wt% polyacrylic acid as a dispersant, 0.9wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 570 MPa for 17 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 5 Pa, an axial pressure of 32 MPa was applied, and the temperature was heated to 510 ° C at a heating rate of 45 ° C / min, kept at this temperature for 14 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 480°C for 29 min, placed in an extruder for extrusion at a speed of 2 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 73% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Comparative Example 3: An aluminum alloy rod, the aluminum alloy rod is composed of a porous composite ceramic skeleton and a modified aluminum alloy, including 93wt% of the modified aluminum alloy and 7wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 16.4wt%; Cu: 4.6wt%; Mg: 0.55wt%; Fe: 0.35wt%; Zn: 0.13wt%; Mn: 0.06wt%; Modifier: 0.43wt%; The balance is Al; The aluminum alloy modifier is composed of the following parts by weight: P: 18 parts; La: 42 parts; Gd: 40 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1 h at a speed of 100 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -24°C for 30 min at a speed of 600 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 5 Pa, and the sample surface temperature is maintained at -20 ° C for 40 h. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 615°C at a heating rate of 8°C / min, keep the temperature for 90min, remove the binder and dispersant, then heat to 1450°C at a heating rate of 7°C / min, keep the temperature for 105min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The composition ratio of the ceramic slurry is: 21wt% cubic boron nitride particles, 19wt% alumina particles, 0.8wt% polyacrylic acid as a dispersant, 0.6wt% gelatin as a binder, and the balance is water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 560 MPa for 15 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 5 Pa, an axial pressure of 37 MPa was applied, and the temperature was heated to 580 ° C at a heating rate of 60 ° C / min, kept at this temperature for 10 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 510°C for 22 min, placed in an extruder for extrusion at a speed of 5 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 50% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Comparative Example 4: An aluminum alloy rod, the aluminum alloy rod is composed of a porous composite ceramic skeleton and a modified aluminum alloy, including 98wt% of the modified aluminum alloy and 2wt% of the porous composite ceramic skeleton; The modified aluminum alloy composition is as follows: Si: 17.8wt%; Cu: 4.2wt%; Mg: 0.49wt%; Fe: 0.44wt%; Zn: 0.14wt%; Modifier: 0.5wt%; Balance is Al; The aluminum alloy modifier is composed of the following parts by weight: P: 14 parts; La: 44 parts; Gd: 42 parts; The porous composite ceramic skeleton is composed of cubic boron nitride and aluminum nitride; The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Add gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grind with a grinder for 1.5 hours at a speed of 120 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry was loaded into a centrifugal device and centrifuged at a temperature of -27°C for 50 min at a speed of 1200 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, vacuumed to 6 Pa, and the sample surface temperature is maintained at -27 ° C for 45 h. After the sample surface is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: firstly heat the green body to 620°C at a heating rate of 7°C / min, keep the temperature for 100min, remove the binder and dispersant, then heat to 1410°C at a heating rate of 6°C / min, keep the temperature for 120min, and then cool to room temperature to obtain a porous composite ceramic skeleton; The ceramic slurry comprises: 20 wt% cubic boron nitride particles, 20 wt% alumina particles, 0.9 wt% polyacrylic acid as a dispersant, 0.7 wt% gelatin as a binder, and the balance water; The preparation method of the aluminum alloy bar is a hot extrusion method, comprising the following steps: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 590 MPa for 13 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body was placed in a plasma discharge sintering furnace, evacuated to 8 Pa, an axial pressure of 35 MPa was applied, and the temperature was heated to 520 ° C at a heating rate of 40 ° C / min, kept at this temperature for 12 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet was kept at 520°C for 25 min, placed in an extruder for extrusion at a speed of 4 mm / s, and cooled to room temperature to obtain an aluminum alloy rod; The porous composite ceramic skeleton has a porosity of 70% and a pore size range of 200 to 300 μm; The particle size of the aluminum alloy particles is 20 to 40 μm. Each embodiment and comparative example was prepared into a sample, and subjected to room temperature tensile test and room temperature low cycle fatigue test on a universal testing machine and a fatigue testing machine, respectively. The hardness was tested with a microhardness tester. The test results are shown in Table 1. Table 1 Mechanical properties test of each embodiment and comparative example name Tensile strength / MPa Elongation / % Hardness / HV Cycle times Example 1 556 17.2 537 59798 Example 2 485 16.1 457 53667 Example 3 539 17.0 505 68735 Example 4 499 16.4 473 64327 Example 5 513 16.5 526 58042 Comparative Example 1 407 15.2 409 36384 Comparative Example 2 422 15.2 420 46796 Comparative Example 3 453 15.8 387 40373 Comparative Example 4 475 15.7 351 42559 In summary, the aluminum alloy rod of the present invention combines the excellent mechanical properties of aluminum alloy and ceramic materials. Compared with the comparative example, it has high strength, high hardness and good fatigue resistance. The preparation process is simple and controllable, and the comprehensive performance is excellent.
Claims
1. A fatigue-resistant aluminum alloy bar, characterized in that: The aluminum alloy rod is composited by 5-10wt% of a porous composite ceramic skeleton and 90-95wt% of a modified aluminum alloy.
2. The fatigue-resistant aluminum alloy bar according to claim 1, characterized in that: The modified aluminum alloy has the following components: Si: 16.0-18.0 wt%; Cu: 4.0-5.0 wt%; Mg: 0.4~0.6wt%; Fe: ≤0.5wt%; Zn: ≤0.2wt%; Mn: ≤0.1wt%; Modifier: 0.4~0.5wt%; The balance is Al.
3. The fatigue-resistant aluminum alloy bar according to claim 2, characterized in that: The aluminum alloy modifier is composed of the following parts by weight: P: 10-20 parts; La: 40-45 parts; Gd: 40-45 parts.
4. The fatigue-resistant aluminum alloy bar according to claim 1, characterized in that: The porous composite ceramic skeleton consists of cubic boron nitride and aluminum nitride.
5. The fatigue-resistant aluminum alloy bar according to claim 1, characterized in that: The preparation method of the porous composite ceramic skeleton is a centrifugal freeze-drying method, comprising the following steps: S11. Slurry preparation: Adding gelatin as a binder, polyacrylic acid as a dispersant, cubic boron nitride particles and aluminum nitride particles to water, grinding with a grinder for 1 to 2 hours at a speed of 100 to 120 r / min to obtain a uniform ceramic slurry; S12. Centrifugal freezing: The slurry is loaded into a centrifugal device and centrifuged at a temperature of -30 to -20°C for 40 to 60 minutes at a speed of 800 to 1200 r / min to obtain a frozen slurry; S13. Vacuum drying: The frozen molded slurry is placed in a dryer that has been cooled, and the vacuum is reduced to 5 to 10 Pa. The surface temperature of the sample is maintained at -30 to -20 ° C for 45 to 50 hours. After the surface of the sample is heated to room temperature, it is demolded to obtain a ceramic green body; S14. High temperature sintering: first heat the green body to 600-620°C at a heating rate of 4-8°C / min, keep it warm for 80-100 minutes, remove the binder and dispersant, then heat it to 1400-1500°C at a heating rate of 6-10°C / min, keep it warm for 100-120 minutes, and finally cool it to room temperature to obtain a porous composite ceramic skeleton.
6. The fatigue-resistant aluminum alloy bar according to claim 5, characterized in that: The composition ratio of the ceramic slurry is: 20-30wt% cubic boron nitride particles, 10-20wt% alumina particles, 0.6-1wt% polyacrylic acid as a dispersant, 0.5-1wt% gelatin as a binder, and the balance is water.
7. The method for preparing the fatigue-resistant aluminum alloy bar according to claim 1, characterized in that: The following steps are involved: S1. Cold pressing: The porous composite ceramic skeleton and the aluminum alloy powder are mixed in proportion and put into a mold for compaction. The hydraulic press is cold pressed at 500-600 MPa for 10-20 seconds to fully fill the aluminum alloy powder into the composite ceramic skeleton to obtain a green body; S2. Plasma discharge sintering: The mold containing the green body is placed in a plasma discharge sintering furnace, evacuated to 5-10 Pa, an axial pressure of 30-40 MPa is applied, and the green body is heated to 500-600 ° C at a heating rate of 40-60 ° C / min, kept at this temperature for 10-15 min, and cooled to room temperature to obtain a sintered green body; S3. Hot extrusion: The sintered billet is kept at 480-520°C for 20-30 min, put into an extruder for extrusion at a speed of 2-5 mm / s, and cooled to room temperature to obtain an aluminum alloy rod.
8. The fatigue-resistant aluminum alloy bar according to claim 7, characterized in that: The porous composite ceramic skeleton has a porosity of 65-75% and a pore size range of 200-300 μm.
9. The fatigue-resistant aluminum alloy bar according to claim 7, characterized in that: The particle size of the aluminum alloy particles is 20 to 40 μm.
Citation Information
Cited By
Anti-fatigue bionic ceramic composite material as well as preparation method and application thereof
CN121085656A